The implementation of government relations of Mizan Publishing House - Muchtar, Khoiruddin; Permana, Achmad Taufan; Marta, Rustono Farady (Universitas Padjadjaran, 2024)
Background: This study examines Government Relations through Little Writers Conference (KPCI) activities carried out by Marketing Communication Mizan Publishing House to establish good relations with the government, namely the Ministry of Education and Culture of the Republic of Indonesia. This research is motivated by the role of the government, which currently influences the flow of national-scale bureaucracy, especially in organizing activity; the government has broad access to publications as a whole. So in an institution or agency, it is necessary to have good relations with the government so that the government can open broad access to programs that the company will carry out. Purpose: The purpose of this research this is, to know the strategy and what move traveled Mizan which performs activities in government relation with Ministry of Education and Culture of the Republic of Indonesia the work of conference little writer Indonesia. Methods: This research used a qualitative approach. The methods used in this research is a case study. Data collection techniques in this research by means of observation participation, the literature study, and depth interview with informants that had been determined. Results: the study, showed that the implementation of Government Relations conducted Marketing Communication Mizan Publishing House consist of two elements which is the formulation of strategy and the implementation of measures. In formulating a strategy, Mizan make creative idea packed through persuasive communication so as to produce the collaboration of program with Ministry of Education and Culture of the Republic of Indonesia. Implementation: Mizan make an audience as the first step and manage his communication formal and nonformal as Implementing the next step. Conclusions: Mizan Government Relations is carried out with a strategy of packaging creative ideas, thereby generating trust from other institutions